Combination of value stream mapping (VSM) method and kanban system to reduce time waste in the production process of making parts for the four-wheel vehicle industry - Pasha, Vebina Sheila; Chin, Jacky (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Fulfilling orders from customers in the automotive industry is a necessity that inevitably causes problems that arise in product delivery to customers due to production delays and decreased production yields. The production process often experiences wasted time in the production process of four-wheeled vehicle spare parts. This research aims to reduce production process time, provide solutions to reduce waste and increase the number of four-wheeled vehicle spare parts produced. This research method uses the Lean Manufacturing (LM) approach by combining the Value Stream Mapping (VSM) method with Kanban system improvements, the application of Root Cause Analysis (RCA), and the Kaizen method. This research found that four factors cause waste in process time, including environmental factors, methods, humans, and machines. This research produces the right solution in the relay out of the Assembly and Final Inspection production processes, as well as the use of the e-kanban system in material and product inventory. The research results have reduced the production process time from 17.10 days to 10.05 days, meaning a decrease of 41.22%. This affected production results which increased from an average monthly production of 42,917 pcs to 60,157 pcs, meaning an increase of 128.65%.